NRF2 -617 C/A Polymorphism Impacts Proinflammatory Cytokine Levels, Survival, and Transplant-Related Mortality After Hematopoietic Stem Cell Transplantation in Adult Patients Receiving Busulfan-Based Conditioning Regimens - Huang, Jingjing; Hao, Chenxia; Li, Ziwei; Wang, Ling; Jiang, Jieling; Tang, Wei; Wang, Lining; Zhang, Weixia; Hu, Jiong; Yang, Wanhua (Frontiers in Pharmacology, 2020)
Busulfan (BU) is widely used in conditioning regimens prior to hematopoietic stem cell transplantation (HSCT). The exposure-escalated BU directed by therapeutic drug monitoring (TDM) is extremely necessary for the patients with high-risk hematologic malignancies in order to diminish relapse,but increases the risk of drug-induced toxicity. BU exposure, involved in the glutathione (GSH) - glutathione S-transferases (GSTs) pathway and proinflammatory response, is associated with clinical outcomes after HSCT. However, the expression of genes in the GSH-GSTs pathway is regulated by NF-E2-related factor 2 (Nrf2) that can also alleviate inflammation. In this study, we evaluated the influence of NRF2 polymorphisms on BU exposure, proinflammatory cytokines levels, and clinical outcomes in HSCT patients. A total of 87 Chinese adult patients receiving twice-daily intravenous BU were enrolled. Compared with the patients carrying wild genotypes, those with NRF2-617 CA/AA genotypes showed higher plasma interleukin (IL)-6, IL-8 and tumor necrosis factor (TNF)-ɑ levels, poorer overall survival (OS; RR= 3.91), and increased transplant-related mortality (TRM; HR= 4.17). High BU exposure [area under the concentration-time curve (AUC) > 9.27 mg/Lh)] was related to BU toxicities. Furthermore, NRF2 -617 CA/AA genotypes could significantly impact TRM (HR=4.04; P=0.0142) and OS (HR=3.69; P=0.0272) in the patients with high BU AUC. In vitro, we found that high exposure of endothelial cell (EC) to BU, in the absence of Nrf2, elicited the hyperstimulation of NF-κB-p65, accompanying with the elevated secretion of proinflammatory cytokines, and led to EC death. These results showed that NRF2 -617 CA/AA genotypes, correlated with high proinflammatory cytokines levels, could predict inferior outcomes in HSCT patients with high BU AUC. Thus, NRF2 -617 CA/AA genotyping in combined with TDM would further optimize personalized BU dosing for sufficient efficacy and safety endpoint.